Penerapan Keselamatan Dan Kesehatan Kerja (K3) Di Wisata Gua Batu Cermin, Labuan Bajo, Kabupaten Manggarai Barat - Jenia, Serlinda; Sastrawan, I Gede Anom (JURNAL DESTINASI PARIWISATA, 2024)
Batu Cermin Cave is one of the natural tourist attractions in Labuan Bajo. Batu Cermin Cave tourism activities eeare inseparable from potential hazards and potential accidents that harm all parties. Therefore, the importance of implementing occupational safety and health procedures. The implementation of health and safety (K3) infrastructure for tourists in the Batu Cermin Cave Tourism Attraction can be seen from three aspects, namely the Human Resources Aspect, the Health and Work Aspect for tourists and workers and the Safety Facility Aspect. The health of tourists in Batu Cermin Cave, before and after visiting the Cave Tourism Attraction is a health aspect. The type of data used in this research is qualitative. The data sources used are primary and secondary data. The research data was collected through interviews, observation and literature study. Qualitative data analysis was carried out to understand the research under study. The results of this study indicate that the procedure for implementing Occupational safety and health in Batu Cermin Cave already exists but is not optimal. Keywords: Application of Occupational Safety and Health Tourism in Batu Cermin Cave